Analysis of a resilient housing project. Quinta da Malagueira (1977) by Álvaro Siza. A lesson to retain - Rodrigues, Ana Luísa (2018)
Back in 1974-75, Portugal had to face a huge housing problem: half a million of Portuguese people had to be reintegrated in the Portuguese society. The decolonization imposed by the end of the dictatorship (called Estado Novo), which stopped controlling the former Portuguese African colonies (Angola, Mozambique, etc.), was the reason behind the return of 500 thousand people to such a small country in less than a year. In fact, they did it honourably. Besides many other solutions, resultant of the generosity of the native people, some housing cost-controlled programs were settle by the Portuguese Government and took place with pragmatism but without thoughtfulness, from the architectural point of view. But some intervention were remarkable. The Quinta da Malagueira (in Évora, 1977) designed by the architect Álvaro Siza was one of those examples. Sustained in a mere economic support (public, private and community help), facing a coherent reading of the place and addressing solutions related to a methodological analysis of suitable and evolving typologies, streaked to a close relationship with the vernacular materials and techniques, this Social Housing Project became an amazing example of success, right from the beginning. Forty years later it is still a success from social, architectural and urbanistic points of view. So what can we learn with the experience of Quinta da Malagueira? What methodological tools did the architect use that should be retained for the sake of consistent and sustainable Architecture? Concerning namely the inevitable housing crisis resulting from post-conflict scenarios of nowadays, this paper aims to analyse the Quinta da Malagueira Project in order to make visible the key of success of this resilient Housing Project, which has been able to deal with the pressure of the adverse circumstances through times, finding architectural, structural and constructive solutions to face it all. To sum up, this paper aims to scrutinize the methodological process in which this project was achieved, to retain the main lessons, seeking the dwelling for the dignity of mankind.